Seminal Plasma Cytokines Are Predictive of the Outcome of Boar Sperm Preservation - Barranco, Isabel; Padilla, Lorena; Pérez-Patiño, Cristina; Vazquez, Juan M.; Martínez, Emilio A.; Rodríguez-Martínez, Heriberto; Roca, Jordi; Parrilla, Inmaculada (Frontiers in Veterinary Science, 2019)
Background: Boar seminal plasma is rich in cytokines, which could influence the capability of spermatozoa to tolerate preservation. Objectives: To evaluate the involvement of boar seminal plasma cytokines in the changes experienced by boar spermatozoa during their storage, either in liquid or frozen state. Materials and Methods: In two separated experiments, semen samples from healthy and fertile boars were split in two aliquots, one centrifuged twice (1,500 ×g for 10 min) to harvest seminal plasma, whereas the other was either commercially extended (3 × 107 sperm/mL) and liquid-stored at 17°C during 144 h (n = 28, Experiment 1) or frozen-thawed using a standard 0.5 mL protocol (n = 27, Experiment 2). Sixteen cytokines were quantified using Luminex xMAP®. Sperm attributes (CASA-evaluated total and progressive motility; flow cytometry-evaluated sperm viability, production of intracellular H2O2 and O2•- and levels of lipid peroxidation in viable spermatozoa) were evaluated either at 0, 72, or 144 h of liquid storage (Experiment 1) or before freezing and at 30- and 150-min post-thawing (Experiment 2). Results: Multiple linear regression models, with Bayesian approach for variable selection, revealed that the anti-inflammatory TGF-β2, TGF-β3, IL-1Ra, and IL-4 and the pro-inflammatory IL-8 and IL-18, predicted changes in sperm motility for liquid-stored semen while the anti-inflammatory IFN-γ was included in the models predicting changes in all sperm attributes for cryopreserved semen. Conclusion: Specific boar seminal plasma cytokines would contribute to modulate the structural and metabolic changes shown by spermatozoa during preservation, either in liquid or frozen state.